Alteration of circulating cell‐free DNA level by external cephalic version: A potential biomarker for direct evaluation of placental damage. Issue 9 (29th June 2021) - Yabuzaki, Keiko; Kamide, Taizan; Ejima, Ruriko; Tsuruoka, Yuto; Sato, Mariko; Kondo, Ibuki; Hasegawa, Akihiro; Sato, Taisuke; Samura, Osamu; Okamoto, Aikou
Abstract: Aim: To confirm that variations in cell‐free fetal DNA (cffDNA) are indicators of external placental damage, we quantitatively investigated cffDNA alterations in maternal peripheral blood during external cephalic version (ECV). Methods: We recruited 48 singleton pregnant women who underwent ECV in our hospital. Before and immediately after ECV, we harvested 10 ml of maternal peripheral blood samples for cffDNA analysis. cffDNA alterations were assessed based on the fetal fraction (FF) rate. We performed ECV without epidural anesthesia but administered epidural anesthesia if ECV was disrupted due to severe pain. Results: The FF increased from 22.9% ± 5.7% to 27.0% ± 5.7% ( p  < 0.05) after ECV. The FF increased in both successful (before, 24.4% ± 5.9%; after, 28.1% ± 5.9%; p  < 0.05) and unsuccessful (before, 21.8% ± 3.8%; after, 27.3% ± 4.2%; p  < 0.05) cases, as well as in patients who received epidural anesthesia (before, 23.9% ± 4.7%; after, 28.5% ± 4.4%; p  < 0.05) or underwent ECV more than once (before, 23.5% ± 6.1%; after, 28.4% ± 5.3%; p  < 0.05). Conclusions: FF alterations increased due to external stresses during ECV; the alterations were markedly greater when the strength and duration of external stress increased. These FF alterations may serve as potential biomarkers for the direct assessment of placental damage.